2020
DOI: 10.1111/obr.13046
|View full text |Cite
|
Sign up to set email alerts
|

Evidence summaries and recommendations from the international evidence‐based guideline for the assessment and management of polycystic ovary syndrome: Lifestyle management

Abstract: Summary Lifestyle is fundamental in chronic disease prevention and management, and it has been recommended as a first‐line treatment in the Australian polycystic ovary syndrome (PCOS) guideline 2011. The first international evidence‐based guideline on PCOS was developed in 2018, which expanded the scope and evidence in the Australian guideline. This paper summarizes the lifestyle recommendations and evidence summaries from the guideline. International multidisciplinary guideline development groups delivered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 103 publications
(131 reference statements)
0
45
0
4
Order By: Relevance
“…The International Evidence-based Guideline for the Assessment and Management of Polycystic Ovary Syndrome (PCOS) emphasizes the importance of diet and PA in the prevention of metabolic and reproductive complications related to PCOS and the role of weight control in overweight and obese PCOS patients. A 5% reduction in body weight is associated with an improvement in both metabolic and reproductive health markers, as well as with psychological benefits [15][16][17]. Patients with PCOS, with improper diet and low levels of PA, are probably more prone to weight gain than the population of healthy women [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Evidence-based Guideline for the Assessment and Management of Polycystic Ovary Syndrome (PCOS) emphasizes the importance of diet and PA in the prevention of metabolic and reproductive complications related to PCOS and the role of weight control in overweight and obese PCOS patients. A 5% reduction in body weight is associated with an improvement in both metabolic and reproductive health markers, as well as with psychological benefits [15][16][17]. Patients with PCOS, with improper diet and low levels of PA, are probably more prone to weight gain than the population of healthy women [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A 5% reduction in body weight is associated with an improvement in both metabolic and reproductive health markers, as well as with psychological benefits [15][16][17]. Patients with PCOS, with improper diet and low levels of PA, are probably more prone to weight gain than the population of healthy women [15,18,19]. As reminded by Eleftheriadou et al and Teede et al, it is not clear whether the prevalence of obesity in the population may affect the prevalence of PCOS [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in women with PCOS show that weight loss achieved by a lifestyle intervention may reduce hyperinsulinemia and thus break the vicious cycle of excessive androgen synthesis [69]. Similar changes occur in obese women who experience weight loss as a result of bariatric procedures.…”
Section: Obesity-related Gonadal Dysfunction In Womenmentioning
confidence: 92%
“…When accompanied by metabolic disorders, such as IR and dyslipidaemia, it can lead to hyperlipidaemia, hypertension, metabolic syndrome and diabetes. In addition, skin problems such as hirsutism and androgenic alopecia cowing to the excessive levels of androgens might also occur (140)(141)(142)(143). Although the pathogenesis of PCOS has not been fully elucidated, recent studies have indicated that excess levels of androgens might be the main pathogenic causative factor of PCOS (144)(145)(146).…”
Section: Effects On Polycystic Ovary Syndromementioning
confidence: 99%